Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

8-epi-11-oxotanzawaic acid A, an undescribed tanzawaic acid analog from the marine fungus Penicillium citreonigrum - Ze-Qing Li; Rong Chao; Si-Yu Fang; Tian-Hua Zhong; Yuan Wang (Phytochemistry Letters, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

Sensitivity analysis and multi-objective particle swarm optimization (MOPSO) of a hollow fiber membrane module for the solar-based heating and humidification system - Si Zeng; Peng Peng; Nan-Feng Li; Cai-Hang Liang; Rong-Hui Qi; Yan-fang Dong; Yu-Kui Men; Jia-Hui Li; Gui-Yin Li (Energy and Buildings, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

Coordination-tailored conductive metal-organic frameworks boost CO2 electroreduction to ethylene for cascade ethylene glycol production - Hui Guo; Shao-Shuai Zhao; Duan-Hui Si; Weijin Li; Zi-Ao Chen; Rong Cao; Roland A. Fischer; Yuan-Biao Huang (Science Bulletin, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Insights into mechanism of jarosite enhanced vanadium (V) bioreduction by Shewanella oneidensis MR-1 and vanadium immobilization in contaminated soil - Li Zhang; Tao Zhang; Rong Guo; Youbin Si (Journal of Hazardous Materials, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Distribution and potential drivers of methane emissions from deep-sea environments in Haima cold seep areas - Li Tang; Jing-Chun Feng; Can-Rong Li; Xiao Chen; Hui Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Introduction Tracing methane originating from deep-sea environments is essential for understanding the global methane budget. However, knowledge regarding the mechanisms governing methane transfer from deep-sea sediments to the water column in cold seep environments remains limited. This study aims to quantitatively investigate the distribution of methane and identify its controlling factors within the Haima cold seep areas. Methods A comprehensive analysis was conducted to investigate the distribution characteristics of methane and its potential drivers in both the water column and sediment porewaters within the Haima cold seep areas. Results The key findings are: (1) Haima cold seeps serve as a methane source to the atmosphere, with pronounced spatial heterogeneity in emission strength across the monitored regions. (2) The vertical distribution of methane is influenced by multiple environmental factors. Key factors in sediment porewaters include sediment depth, porosity, inorganic carbon (IC), chloride (Cl – ), and sulfate (SO 4 2– ), whereas silicate (SiO 3 2– ) and dissolved oxygen (DO) are primary regulators in the water column. (3) Sediments represent a significant methane source for bottom seawater, with methane consumption being more pronounced in seepage areas than in non-seepage areas. Discussion This study demonstrates that methane dynamics in the Haima cold seep are complex and driven by a combination of physical, chemical, and biological processes across the sediment–water interface. The identified key drivers underscore the importance of porewater geochemistry and water column biogeochemistry in controlling methane release. These findings significantly advance our understanding of methane transport in deep-sea seep systems and provide crucial insights for refining global methane flux estimates.

One new rearranged pyranone derivative with antibacterial activity from Xylaria curta YSJ-5 - Shan-Shan Wei; Dao-Jun Rong; Jia-Ying Lai; Chen Chen; Si-Ran Li; Zhong-Hua Yu; Hai-Bo Tan (Phytochemistry Letters, 2025)

Concentration-dependent visual SO2 detection from trace to pure in a zirconium MOF - Guang-Rui Si; Xiang-Jing Kong; Lin-Hua Xie; You-Tuo Zhang; Tao He; Jian-Rong Li (Science Bulletin, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Biochar supported metal cobalt activated PAA to efficiently degrade CBZ: The important role of Co (IV) in the generation of peroxyacyl radicals - Mengyu Li; Shaochun Yuan; Yuhang Liu; Siqi Chen; Mingyang Si; Rong Liu; Bangxing Ren; Zhe Zhang; Zhen Liu (Journal of Water Process Engineering, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

A new sesquiterpene from endophytic fungus Colletotrichum sp. B-89 - Ke-tao Zhang; Bing Zhang; Zhi-pu Huang; Yu-xiao Xu; Xiao-rong Xu; Si-heng Li; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2025)

Steering CO2 electroreduction to hydrocarbons over 2D thiol-based conductive metal-organic framework - Qiu-Jin Wu; Duan-Hui Si; Yu-Liang Dong; Qian Chen; Li-Li Han; Rong Cao; Yuan-Biao Huang (Science Bulletin, 2025)

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Methane seepage leads to a specific microplastic aging process in the simulated cold seep environment - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Bin Wang; Can-Rong Li; Yi-Lei Lin; Yong-Ji Huang; Song Zhong; Xiao-Chun Zhang; Jun-Lin Hu; Si Zhang (Journal of Hazardous Materials, 2025)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Early detection of fungal infection in citrus using biospeckle imaging - Si Yang; Chenxi Li; Xinyu Li; Jingying Jiang; Yansong Zhao; Xiaoli Wang; Wenliang Chen; Rong Liu; Kexin Xu (Computers and Electronics in Agriculture, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Construction of large-aperture mesoporous silica spheres supported polyoxometalate heterogeneous catalysts and their high-efficiency for the ultra-deep desulfurization - Jia-Qi Wu; Lu-lu Ma; Zhuang-Zhuang Li; Xin Li; Si-Wen Li; Chang Li; Rong-Xi Li; Jian-She Zhao (Fuel, 2024)

Enhanced waste Plastics-to-Power in situ conversion through iron oxide as pseudofuel in solid oxide fuel cells - Rong Zhang; Wenting An; Yanxia Guo; Yong Jiao; Si-Dian Li; Fangqin Cheng (Fuel, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Exploring carbon content variation in microplastics sequestrated from seawater to sediment in the Haima cold seep area - Xiao-Nan Wu; Jing-Chun Feng; Xiao Chen; Can-Rong Li; Si Zhang (Journal of Hazardous Materials, 2024)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Formation mechanisms of N2O and NH3 on Pd/ZrO2 and Pd/Al2O3 for NO reduction - Houlin Wang; Yue Peng; Bin Zhou; Jin Yuan; Rong Wang; Wenzhe Si; Junhua Li (Chemical Engineering Journal, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Saliva proteome of partially- and fully-engorged adult female Haemaphysalis flava ticks - Lei Liu; Rong Cheng; Si-qing Mao; De-yong Duan; Li-li Feng; Tian-yin Cheng (Veterinary Parasitology, 2023)

Mechanistic insights into effect of in-situ microplastics on heavy metals leaching behavior from its dyeing sludge incineration bottom ash - Xiaoao Shi; Hao Rong; Jinping Li; Yifan Zhao; Lu Ren; Si Chen; Jingxin Liu; Meng Mei; Yongjie Xue; Teng Wang (Journal of Environmental Chemical Engineering, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

An antioxidant lignan glycoside and triterpenoid saponins from the leaves of Synsepalum dulcificum - Xin-Peng Li; Jun-Fei Wang; Rong Huang; Tang-Chang Xu; Si-Si Liu; Qing-Rong Yang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Rapid charge transfer in covalent organic framework via through-bond for enhanced photocatalytic CO2 reduction - Li-Juan Gong; Li-Yao Liu; Shao-Shuai Zhao; Shuai-Long Yang; Duan-Hui Si; Qiu-Jin Wu; Qiao Wu; Yuan-Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

Rapid, linear, and highly reliable structural-color switching enabled by thermal regulation of chiral nematic mesophases - Dong Li; Rong-Rong Jiang; Si-Kai Chen; Jia-Min Wu; Xiu Dong; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

First report of Botryosphaeria dothidea causing leaf blotch of Mahonia bealei in China - Yi-Jia Cao; Rong-Han Chen; Yuan-Zhi Si; Li-Hua Zhu (Journal of Plant Pathology, 2022)

Utilization of pre-existing competent and barren quartz veins as hosts to later orogenic gold ores at Huangjindong gold deposit, Jiangnan Orogen, southern China - Liang Zhang; David I. Groves; Li-Qiang Yang; Si-Chen Sun; Roberto F. Weinberg; Jiu-Yi Wang; Sheng-Gang Wu; Lei Gao; Lan-Ling Yuan; Rong-Hua Li (Mineralium Deposita, 2020)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Reference evapotranspiration concentration and its relationship with precipitation concentration at southern and northern slopes of Tianshan Mountains, China - Fa-rong Huang; Tao Yang; Qian Li; Si-si Li; Lan-hai Li; Suwannee Adsavakulchai (Journal of Mountain Science, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Carbonate formation mechanism in paleosol sediments of the Bohai Sea coastal zone, China - Shuhuan Du; Baosheng Li; Rong Xiang; Dongfeng Niu; Yuejun Si (Arabian Journal of Geosciences, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

The mediating and moderating role of personal strain and coping resource in the relationship between work stressor and quality of life among Chinese nurses - Si-Ying Wu; Huang-Yuan Li; Shu-Juan Yang; Wei Zhu; Xiao-Rong Wang (International Archives of Occupational and Environmental Health, 2012)

cDNA cloning and characterization of 5′ upstream promoter region of porcine mef2c gene - Min Liu; De Quan Xu; Jian Peng; Rong Zheng; Fenge Li; Si Wen Jiang (Molecular Biology Reports, 2011)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)